If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying x + -35 = 4x Reorder the terms: -35 + x = 4x Solving -35 + x = 4x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-4x' to each side of the equation. -35 + x + -4x = 4x + -4x Combine like terms: x + -4x = -3x -35 + -3x = 4x + -4x Combine like terms: 4x + -4x = 0 -35 + -3x = 0 Add '35' to each side of the equation. -35 + 35 + -3x = 0 + 35 Combine like terms: -35 + 35 = 0 0 + -3x = 0 + 35 -3x = 0 + 35 Combine like terms: 0 + 35 = 35 -3x = 35 Divide each side by '-3'. x = -11.66666667 Simplifying x = -11.66666667
| (4x-9)/(7x^2+9x) | | -4-(5-3p)= | | x-3/4-2=x-2/3 | | 5.3x+4=4.3x | | 34=5x+16x^2 | | 6x-(-3x+9)=(x-7)-4(9x-9) | | (4x-9)/(7x^2+9) | | 5[x]=45 | | 5n+1=5(n-1) | | 8(k+11)-6k=9 | | 3u+4=22 | | 16x^2+5x=0 | | 7x+21=2x+56 | | 20y^2-15y^3= | | 1/4(x-3)=1/3(x-2) | | f(x)=5-.2x | | c/8+230/8=200 | | 22/1 | | 5r^2-16r+12= | | -5y-9=4y+2 | | 3k+34=4(6+3k)+1 | | -6-(-2n)=3-6+5 | | 15-2x=-19 | | .11x-.03(40000-x)=760 | | 5d+11=8d-7 | | 3x-2y+5y-8x= | | -2(x-5)-3x=120 | | (57/2)x=26.8 | | -2.3-5x-4.1-3x=-7x+1.6 | | 2(3m-4)=8m-11 | | -2(-2)+4(4)=8 | | -3(2x+4-3-6x)-2=10x |